The pathogenesis of benign prostatic hyperplasia and the roles of Prdx3, oxidative stress, pyroptosis and autophagy:a review - Xiang, Junjie; Zheng, Yuxuan; Chen, Diang; Zeng, Yining; Zhang, Jingqi; Chang, Degui; Chang, Cheng (Frontiers in Oncology, 2025)
Benign prostatic hyperplasia (BPH) is driven by hormonal and inflammatory mechanisms, yet emerging factors such as peroxiredoxin 3 (Prdx3), oxidative stress (OS), pyroptosis, and autophagy remain understudied. This review synthesizes their roles in BPH pathogenesis. We demonstrate that Prdx3 inhibits autophagy, exacerbates OS, and induces pyroptosis, ultimately promoting prostate cell proliferation. Paradoxically, while Prdx3 mitigates OS, its interaction with autophagy amplifies oxidative damage. These findings challenge conventional antioxidant therapies, suggesting that enhancing antioxidant capacity may inadvertently worsen BPH progression. Our analysis provides novel insights into therapeutic strategies targeting these pathways.